The Effect of Acids on Alkaloid Yield in Pressurized Water Extraction of Narcissus Pseudonarcissus - Orchidea Rachmaniah; Jaap van Spronsen; Robert Verpoorte; Geert Jan Witkamp (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Pressurized water (PW) extraction of galanthamine from Narcissus pseudonarcissus bulbs was performed. The obtained yield was compared with the yield from conventional acidified water extraction and methanolic Soxhlet extraction. Both PW and conventional acidified water extraction were followed by a subsequent purification step for the alkaloids. The PW extraction (70 °C, 150 bar, 45 min) yielded as much galanthamine as methanolic-Soxhlet extraction (ca. 3.50 mg/g). Meanwhile, acid-base extraction with 1% of HBr (v/v) at 65 °C for 3 h gave a lower yield (ca. 2.65 mg/g). A higher PW temperature did not significantly increase the galanthamine yield. Pressure increase is not necessary since more water-soluble compounds such as proteins and polysaccharides are co-extracted, resulting in high viscosity of the water extract solution, which hampers the filtration process. Hence, the acidity of the solution is highly important both in the case of PW extraction and acidified water extraction. Besides galanthamine, the total alkaloid profile following Narcissus alkaloids was also obtained. Lycoramine, O-methyloduline, norgalanthamine, epi-norgalanthamine, narwedine, oduline, haemanthamine, O-methyllycorenine, and a haemanthamine derivate were identified. Although a high yield was obtained from PW extraction, the further purification needs to be improved to obtain an economically feasible industrial extraction process.